2014
DOI: 10.1080/01919512.2013.836447
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Experimental Validation of a Model for the Kinetics of Ozone and Hydroxyl Radicals with Natural Organic Matter

Abstract: Accepted: 15 Jul 2013International audienceA unified model for the kinetics of O3 and *OH with NOM was proposed, calibrated and validated based on large experimental data sets. Single-phase batch experiments were done on 11 water samples from seven resources. Seasonal variations were studied on three resources. Effects of reaction time with ozone, ozone dose, pH, temperature, radical scavenger adding, and NOM dilution were studied. The experiments represented more than 1200 and 900 concentration measurements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…When designing new or upgrading existing ozonation processes, quantitative understanding of the effects of variations in water quality due to seasonal changes or pretreatment processes (in other words, pre-ozonation vs. main ozonation) on the ozone decomposition (IOD and k sec ) and OH radical formation or reaction kinetics (Ω or R ct ) is important. This information is limited in the literature (Elovitz and Von Gunten 1999;Elovitz, Von Gunten, and Kaiser 2000a;Hoigné and Bader 1994;Mandel, Roche, and Wolbert 2014). Especially, the influence of variations in water quality on the Ω parameter has rarely been investigated.…”
Section: Introductionmentioning
confidence: 94%
“…When designing new or upgrading existing ozonation processes, quantitative understanding of the effects of variations in water quality due to seasonal changes or pretreatment processes (in other words, pre-ozonation vs. main ozonation) on the ozone decomposition (IOD and k sec ) and OH radical formation or reaction kinetics (Ω or R ct ) is important. This information is limited in the literature (Elovitz and Von Gunten 1999;Elovitz, Von Gunten, and Kaiser 2000a;Hoigné and Bader 1994;Mandel, Roche, and Wolbert 2014). Especially, the influence of variations in water quality on the Ω parameter has rarely been investigated.…”
Section: Introductionmentioning
confidence: 94%
“…The kinetics of ozone decomposition has been modeled by other researchers before. ,, Tomiyasu et al used an accumulated stopped-flow method, and Mandel et al conducted single-phase batch experiments to validate their obtained results . Both studies implemented almost the same kinetic model and reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Although the chemistry of the reaction has been investigated in the gas phase, only the equilibrium constant has been measured in an aqueous phase, , and there is a lack of reported kinetic data for forward and backward reactions. The equilibrium constant is directly measured by a number of researchers , and has been referred to and used in many studies. Although some studies have reported that the p K a can vary with ionic strength, Bielski et al have shown that p K a is invariant within experimental error when the concentration of is less than 0.01 kmol m –3 , which is a valid assumption for this study. Bezbarua and Reckhow reported rate constants of 3.2 × 10 5 s –1 and 2 × 10 10 m 3 kmol –1 s –1 for the forward and backward reactions, respectively; however, these constants are based on the equilibrium constant assuming that the backward reaction is at the diffusion limit.…”
Section: Introductionmentioning
confidence: 96%
“…The ozone reactivity of bulk organic matter varies depending on the origin and characteristics of the sample, and typically covers a range of several orders of magnitude. 76 Different fractions of dissolved organic matter promote or inhibit ozone decay and the production of OH radicals, leading to different ozone and OH radical exposures. 16,77 The characteristics of the organic matrix, such as aromaticity, protein and humic acid content, were not determined in this study.…”
Section: Removal In Tap Water and Wastewater Effluentmentioning
confidence: 99%